Evaluación de las políticas laborales en la Empresa Sumifru Ecuador S.A. - Tello Mendoza, Maholy Narcisa (2021)
Labor policies play a leading role for internal regulation in the development of business activities of organizations, because they establish necessary guidelines that positively or adversely condition the organizational culture, for this reason the correct application or absence of internal policies in the company Sumifru Ecuador SA causes the management of human talent not to implement strategic evaluation indicators that regulate the internal procedures of the administrative and operational activities of the Hacienda San Luis, which is why the objective of the investigation is to analyze the policies labor owned by Sumifru Ecuador SA in the development of business skills. The methodology of the study is made up of the types of field and descriptive investigations that facilitated the obtaining and ordering of all the information obtained, in addition, the methods used are inductive and synthetic, whose contribution lies in the identification of the main facts problematic, while the techniques used were interviews and surveys, which allowed to know the perception of the primary sources of research on internal work policies. The conclusions of this study reveal that the policies that the institution does not comply with are occupational safety and administration with respect to the hiring of human talent, while it only has a correct application in its quality policy, a context that shows that not all labor policies have an exhaustive control in business management.